Praktik Pengelolaan Sampah Berbasis Masyarakat di Kelurahan Tobek Godang - Ahmad Jamaan; Siti Nursiah; Shalika Putri Amanda; Hilwa Nafihatuzzahro; Lucia Natasya Agatha; Kanaya Adia Zahrani; Marctha Olivia Hutagalung; Zia Azzahra Al Haq; Nabila Ardani Syam; Aulya Yulianti; Ryndi Aida Permata; Syaira Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Waste management remains a serious environmental issue, including in Tobek Godang Village, Pekanbaru. The lack of community awareness in separating organic, inorganic, and hazardous waste has resulted in suboptimal household waste management practices. This community service program aims to improve residents’ understanding and skills in waste separation and processing through socialization and training activities. The methods applied consisted of a questionnaire survey with 66 respondents, field observations, group discussions, and hands-on composting practice as part of a participatory approach. The results indicate an increase in community awareness, demonstrated by the provision of separate bins for organic and inorganic waste, better understanding of plastic recycling codes, and the ability to produce quality compost characterized by loose texture, dark color, and earthy aroma. The program’s sustainability is reflected in the community’s commitment to consistently apply environmentally friendly practices, potentially creating a multiplier effect in household-based waste management. Thus, this program can serve as a model of community empowerment in supporting environmental cleanliness and the achievement of local SDGs